Analysis of Coach’s Leadership Style on Individual Athlete Satisfaction - Farhansyah, Afif; Fitri, Mustika; Hamidi, Ahmad (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
The coach's leadership has a big influence on the athlete's motivation, enthusiasm, and self-confidence in achieving the set goals. An effective leadership style in a sports context has a significant impact on athlete motivation and performance. Therefore, it is important to understand athletes' perceptions and satisfaction with their coach's leadership style. This study aims to analyze the effect of the coach's leadership style on individual athlete satisfaction by using the Leadership Sport Scale (LSS) questionnaire to measure the coach's leadership style and the Satisfaction Scale For Athletes (SSA) questionnaire to measure athlete satisfaction. This study uses a quantitative descriptive with a survey test method. The sample in this study were Student-Athletes of UKM Pencak Silat UPI in the sparring category and the single art category and sparring category, totaling 40 people. The data analysis technique uses the coefficient of determination test (R Square) with the aim of determining the effect of the coach's leadership style on athlete satisfaction. The results of data analysis show that the coach's leadership style affects individual athlete satisfaction with a percentage of 58%. Based on data processing and statistical analysis in this research, it can be concluded that there is an influence between the coach's leadership style on the level of individual athlete satisfaction.